PENGARUH PROMOSI, KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SMARTPHONE MEREK VIVO DI BENGKULU - Raaitulisari, Raaitulisari; Bahrun, Khairul (UM. Bengkulu, 2025)
The aim of the research is to determine the influence of promotion, product quality and price on purchasing decisions for Vivo brand Smartphone products (Case study of students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu) and to find out which factors most dominantly influence purchasing decisions. This research used quantitative methods on 105 respondents. The population used in this research were consumers of Vivo brand Smartphone products among students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu and sampling in this research was a non-probability sampling technique. The results of the research concluded that Promotion, Product Quality and Price had a positive and significant effect partially or simultaneously on Purchase Decisions for Vivo brand Smartphone products among students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu.Keywords: Promotion, Product Quality, Price, Purchasing Decisions